Listening and speaking skills - Cusack, Barry (Macmillan, 2007)
"Improve your IELTS Skills" is aimed at students between bands 4.5 and 7.5. The series has three preparation courses, Academic Reading, Academic Writing, and Listening and Speaking. The courses develop language, skills and test techniques to help students achieve a higher IELTS score.